Agenda for meeting on 17 August 1938
043-0060-001 There will be a Meeting of the Spanish Medical Aid Committee on Wednesday next the 17th August at 24, New Oxford Street at 8.45 p.m. AGENDA:- 1. Minutes of the Previous meeting. 2. Matters arising. 3. Special Correspondence. 4. Report of the Personnel and Technical Sub-Committee. 5. Report of the Organising Sub-Committee. 6. Any other business. Note:- The Organising Sub-Committee will meet at 7.30 p.m. 292/946/43/60